Religious Harmony in the Era of Globalization: Social Interaction of Muslim and Christian Religions in Pelang Village, Lamongan - Umi, Feryani; Ichwayudi, Budi (Tribakti: Jurnal Pemikiran Keislaman, 2022)
Religious harmony is a coveted hope in building a nation and state community in an effort to achieve a safe, peaceful, and prosperous life. The interaction of people who have different beliefs is not a trivial matter to be addressed. However, collective awareness is needed to understand the importance of harmony in building community life with various religions. This study takes the theme of the role of local culture in preserving harmony, as well as the impact of globalization on inter-religious relations in Pelang Lamongan Village. The purpose of this research is to understand the role of local culture in preserving religious harmony, and to know the impact of globalization on inter-religious relations in the Pelang Lamongan village community. As for the analysis knife, this research uses the Trilogy theory of religious harmony, Mukti Ali, with the model of internal harmony between religious communities, inter-religious communities, and religious communities with the government. Research using a qualitative approach seeks to examine more deeply the pattern of inter-religious harmony in the village of Pelang Lamongan. With the findings, that culture is one of the efforts to build religious harmony such as local traditions, namely earth alms and life cycle rites, they become routines that they do continuously and continuously. This directly or indirectly has the consequence that it can foster and strengthen inter-religious harmony. An inclusive religious attitude also underlies the tolerant attitude of the Pelang village community, this attitude is manifested in the practice of gotong royong in carrying out socio-religious activities involving Muslims (NU, Muhammadiyah) and Christians. In addition, globalization can be used as capital in strengthening the intensity of social interaction among the people of Pelang Lamongan village.